Perancangan dan Pembuatan Website Majelis Ulama Indonesia Kota Batu Malang - Farokhah, Lia; Noercholis, Achmad; Ahda, Fadhli Almu’iini; Sulistyo, Danang Arbian; Rofiq, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Community service is one of the activities required for lecturers at Institut Teknologi dan Bisnis ASIA Malang every semester. This activity is carried out in groups to distribute knowledge to the community. This activity is in partnership with the Batu City MUI in creating a digital website for distribution of information to the wider community. Problems arise when a partner's website is hacked or damaged by a hacker. The service team wanted to teach how to recover or mitigate after damage, but the technical team could not provide information regarding the website and suggested creating a new website. In the initial stage, this service will create a new website. The method of this service approach is to carry out discussions in group discussion forums (FGD). The results of the discussion were realized in the form of a website for the Batu City MUI. Evaluations were carried out regarding design and functionality requirements. The partners are satisfied but it must be developed further. In ongoing collaboration this website will continue to be developed. After that, training in mitigating data when exposed to hackers will be carried out in the next service.